Constantine and the Cities : Imperial Authority and Civic Politics - Lenski, Noel Emmanuel, 1965- (Book collections on Project MUSE., 2016)
Roman Emperor Constantine raised Christianity from a minority religion to imperial status, but his religious orientation was by no means unambiguous. In Constantine and the Cities, Noel Lenski demonstrates how the emperor and his subjects used the instruments of government in a struggle for authority over the religion of the empire.